The impact of an empowering school leadership on teachers’ organizational effectiveness outcomes and the role of ICTs - Karagianni, Eleni; Papadaki, Angeliki; Karabatzaki, Zoe; Driga, Anna Maria (Eximia, 2023)
Nowadays, in order to take steady steps towards the transformation of the modern school, the transition from the hierarchical model of school administration to a participatory leadership model, sharing of control and responsibilities is required, which focuses on the teachers’ empowerment, through the provision of chances for motivation, autonomous action and professional development. The aim of this paper is to study the supportive mechanisms of teachers’ empowerment, which is developed by a school principal who acts as a leader, in order to cope with their multiple responsibilities, contributing, dynamically, to the success of the school organization’s mission. The results of this study showed that a school leadership, which creates quality opportunities for teacher’s empowerment, has a catalytic impact on their active engagement, joint commitment, cooperation, innovative and inquisitive attitude, job satisfaction, but also on the high achieving of their students, contributing, essentially, to the restructuring of the educational field.